Originally Posted by

**strik3r** You initially got the equation of the circle wrong.

The equation is (X-2)sqr + (y+3)sqr = Rsqr-------------(1

But since the circle passes through (1,4) sub it into equation (1

so you get

(1-2)sqr + (4+3)sqr = Rsqr

1 + 7sqr = Rsqr

50 = Rsqr

R = 5Root 2

*** sqr = Squared

Always remember that if a line or any shape passes through a point, the equation must be satisfied when you sub that point into that equation. like what i did above

hope it helped

ask me if u have any further questions